An Approach to Data Processing for the Smart District Heating System - A. V. Sednin; A. V. Zherelo (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article deals with the district heating systems transition to intelligent systems by developing a united information system and obtaining a high level of controllability of the entire system. During the implementation of automated control systems of district heating, a number of information tasks of the lower level are being introduced, including the data collection for thermal and hydraulic modes of operation for monitoring, operational management and analysis of the effectiveness. One of the problems of intelligent systems is data collection and its further storage and processing. Methods for data collection for real energy facilities are considered and the usage of multi-level system with the allocation of the upper level in the cloud storage has been proposed. In addition to the currently implemented data collection scheme in automated control systems, a generalized method of data acquisition with the introduction of duplicate streams has been proposed to ensure their integrity. The paper presents the approaches to identifying the collected data, ensuring the stability of the collection process, reliability of data storage and their integrity. Role-based security model with a dedicated single certification authority helps to protect data. Approaches to further processing of the collected data are shown, differing in the way of parallel data processing. The next stage of development is global monitoring systems that will be aimed to prompt response at all levels. The accumulated data will allow bringing the operating systems to a new level through the use of tools such as forecasting and simulation modeling, which will allow creating digital twins of heat supply systems. The proposed data collection system will perform forecasting and modeling at a higher level, and, as a result, help in the formation of more balanced management decisions.